Passion Fruit Problems in the Home Landscape - Amir Rezazadeh; Mark T. Bailey; Ali Sarkhosh (EDIS, 2020)
In Florida, purple and yellow passion fruit have been widely cultivated by homeowners for years, and south Florida’s subtropical climate allows for growing passion fruit year-round. Many factors affect longevity and productivity of passion fruit vine, including environmental stresses, pests, and disease. This new 5-page document is designed to help Master Gardeners and homeowners by answering commonly asked questions about passion fruit production problems. Written by Amir Rezazadeh, Mark Bailey, and Ali Sarkhosh, and published by the UF/IFAS Horticultural Sciences Department. https://edis.ifas.ufl.edu/hs1397